7th International Symposium on Superalloy 718 and Derivatives (2010) 2010
DOI: 10.7449/2010/superalloys_2010_893_905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the LCF Loading Cycle Characteristics on the Fatigue Life of Inconel 718 at High Temperature

Abstract: A series of both stress-controlled and strain-controlled low cycle fatigue tests were conducted on alloy Inconel 718 to investigate the impact of various parameters on the behaviour of the material. Namely, focus was placed on the influence of major parameters such as the cycle frequency, the strain/stress rate, the holding time at various stress levels, the stress relaxation and the fatigue stress ratio. A detailed characterisation of the fatigue-induced rupture surfaces was performed to analyse the role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…Additional δ phase also precipitated within grains due to GBE processing, observed for the GPD condition. This is consistent with reported observations in studies of 718, which showed that δ phase preferentially nucleates at slip bands produced by plastic deformation [19].…”
Section: Microstructure-property Relationshipssupporting
confidence: 93%
See 1 more Smart Citation
“…Additional δ phase also precipitated within grains due to GBE processing, observed for the GPD condition. This is consistent with reported observations in studies of 718, which showed that δ phase preferentially nucleates at slip bands produced by plastic deformation [19].…”
Section: Microstructure-property Relationshipssupporting
confidence: 93%
“…2). This is likely due to preferential δ phase nucleation at slip bands after plastic deformation, as sometimes observed for 718 [19]. For all conditions, precipitates were distributed uniformly within grains, and preferential coarsening or denuding of precipitates was not typically observed at grain boundaries, Fig.…”
Section: Resultssupporting
confidence: 55%
“…To our knowledge, all the simulations of ring-rolling published up to now (ours included) have been performed using constitutive equations obtained from monotonic tests (compression or torsion tests). We have not found any data of the constitutive behaviour of 718 alloy under either ratcheting or low-cycle fatigue conditions at temperatures as high as those required for hotworking (nor under conditions of a monotonic deformation with a superimposed cyclic one); however, available data for lower temperatures, of interest in aeroengine operation, show an important difference between monotonic and cyclic behaviour (e.g., significant LCF softening at 650°C, [24][25][26][27][28][29][30]). Consequently, we believe that a study of the constitutive behaviour o f the 718 alloy in conditions close to those found in the industrial ring-rolling operation is worth being undertaken for attempting to optimize such a promising process.…”
Section: Discussionmentioning
confidence: 99%
“…Some materials show better durability at compressive hold, and some show better durability during tensile hold. Taina et al did a study with disproportionate hold time at maximum and minimum strain for forged IN 718. It was inferred from their study that the hold time at minimum strain is fixed and extending the hold time at maximum strain will not decrease the fatigue life of material.…”
Section: Introductionmentioning
confidence: 99%